2020
DOI: 10.1038/s41419-020-02862-7
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyl-D-glucosamine kinase binds dynein light chain roadblock 1 and promotes protein aggregate clearance

Abstract: Emerging evidence indicates that neurodegenerative diseases (NDs) result from a failure to clear toxic protein aggregates rather than from their generation. We previously showed N-acetylglucosamine kinase (NAGK) promotes dynein functionality and suggested this might promote aggregate removal and effectively address proteinopathies. Here, we report NAGK interacts with dynein light chain roadblock type 1 (DYNLRB1) and efficiently suppresses mutant huntingtin (mHtt) (Q74) and α-synuclein (α-syn) A53T aggregation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…The pull-down assay followed by immunoblotting with respective antibodies showed that exogenous NudC interacted with endogenous NAGK ( Figure 1 B). As both NAGK and NudC were reported to interact with dynein by previous studies [ 16 , 28 ], we also checked the presence of dynein components. Interestingly, both DYNLRB1 and light intermediate chain 1 (DYNC1L1) were found to interact with exogenous NudC.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The pull-down assay followed by immunoblotting with respective antibodies showed that exogenous NudC interacted with endogenous NAGK ( Figure 1 B). As both NAGK and NudC were reported to interact with dynein by previous studies [ 16 , 28 ], we also checked the presence of dynein components. Interestingly, both DYNLRB1 and light intermediate chain 1 (DYNC1L1) were found to interact with exogenous NudC.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, this DYNLRB1 interaction domain is also the NAGK binding site, as indicated in our previous report [ 29 ]. Furthermore, our molecular modeling and cell biological studies showed that residues 59 to 69 in the small domain of NAGK are major hotspots for the NAGK–DYNLRB1 interaction [ 28 ]. Therefore, there seems to be binding competition between NAGK and IC for DYNLRB1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations